Crystal defect modulation in cathode materials for non-lithium ion batteries: Progress and challenges. (May 2021) - Xiong, Fangyu; Tan, Shuangshuang; Yao, Xuhui; An, Qinyou; Mai, Liqiang
Graphical abstract: Abstract: Non-lithium ion (Na/K/Mg/Ca/Zn/Al-ion) batteries (NLIBs) have stepped into the spotlight as alternatives or supplements to lithium-ion batteries in large-scale energy storage systems with the aid of vast advantages in resource and production cost. In the past years, a lot of efforts have been taken to develop high-performance cathode materials for various NLIBs by exploiting new cathode materials or optimizing the existing categories. As an efficient optimizing strategy to break the bottleneck of intrinsic lattice, crystal defect modulation attracts much attention and has been applied in many cathode materials. Suitable crystal defects in cathode materials could enhance the electrochemical reactivity, electronic conductivity, ionic diffusivity, and structural stability, then improving the capacity, rate performance and cycling stability of batteries. In this review, the investigations of crystal defect modulation in cathode materials for NLIBs are systematically summarized by highlighting some typical and recent progresses. The positive effects and improvement mechanism of intentionally introduced defects, including substitutional impurity, interstitial impurity, vacancy defect, cation disorder and amorphization, are discussed. Besides, the challenges and the perspectives about future directions of crystal defect modulation on the cathode materials for NLIBs are presented.